Enhancing Mechanical Properties of Hemp and Sisal Fiber-Reinforced Composites Through Alkali and Fungal Treatments for Sustainable Applications - Rahul Kovuru; Jens Schuster (Journal of Manufacturing and Materials Processing, 2025)
The growing demand for sustainable materials has driven interest in natural fiber-reinforced composites as eco-friendly alternatives to synthetic materials. This research investigates the fabrication and mechanical performance of hemp and sisal fiber-reinforced composites, with a focus on improving fiber–matrix bonding through alkali and fungal treatments. Experimental results show that fungal treatment significantly improves tensile and flexural strength, while hardness slightly decreases. Water absorption tests revealed moderate reductions in hydrophilicity compared to untreated samples, although absolute water uptake remains higher than conventional glass/epoxy composites. Microscopy analysis further confirmed enhanced fiber adhesion and structural integrity in treated specimens. These findings suggest that hybrid composites reinforced with hemp and sisal, particularly with fungal treatment, hold promise for low-to-medium load sustainable applications in the automotive interiors, packaging, and construction industries, where moderate mechanical performance and partial biodegradability are acceptable. This research contributes to the advancement of bio-based composite materials while acknowledging current limitations in long-term durability and complete biodegradability.